Total Synthesis, Stereochemical Assignment, and Divergent Enantioselective Enzymatic Recognition of Larreatricin. Issue 59 (1st October 2018) - Martin, Harry J.; Kampatsikas, Ioannis; Oost, Rik; Pretzler, Matthias; Al‐Sayed, Emir; Roller, Alexander; Giester, Gerald; Rompel, Annette; Maulide, Nuno
Abstract: A concise and efficient total synthesis of the lignan natural product larreatricin as well as an unambiguous assignment of configuration of its enantiomers are reported, resolving a long‐held controversy. Enzyme kinetic studies revealed that different polyphenol oxidases show high and remarkably divergent enantioselective recognition of this secondary metabolite. Abstract : Recognize your mirror image : We report an efficient total synthesis of the lignan natural product larreatricin as well as an unambiguous assignment of configuration of its enantiomers. Enzyme kinetic studies reveal that different families of polyphenol oxidases show high and remarkably divergent enantioselectivity in their recognition of this secondary metabolite.